Nine Seventeenth-Century Organ Transcriptions from the Operas of Lully - Howell, A. C. (Almonte Charles), 1895-1986 (Book collections on Project MUSE., 2015)
Jean-Baptiste Lully is perhaps best known in the history of music as the founder of French opera. Although Italian-born himself, he created a form of opera so suited to French tastes and needs that it alone, among the attempts of various other nations at operatic forms of their own, was able to resist domination by Italian opera and to maintain its individual identity during the seventeenth and eighteenth centuries. The impress he made upon French music was enormous, and it affected every musical medium of his day. Evidence of his influence in a field as remote from his own as the literature f.